Study of the TiO2 effect on the heavy metals oxides borosilicate glasses structure using gamma-ray spectroscopy and positron annihilation technique. (November 2019) - Alharbi, T.; Mohamed, Hamdy F.M.; Saddeek, Yasser B.; El-Haseib, Ahmed Y.; Shaaban, Kh S.
Abstract: Fourier transform infrared (FTIR), γ-ray attenuation and positron annihilation lifetime (PAL) spectroscopies were performed to study the physical and nanostructure properties of prepared Na2 O-B2 O3 –PbO–SiO2 –Bi2 O3 (NBSi) glasses with different concentration of TiO2 . The FTIR spectra of alkali lead titanate borosilicate glasses had different ratios of Bi2 O3 are analyzed. The detailed examination revealed a creation of BO4 on the expense of BO3 and BiO3 structural units. This process with the increment of Bi2 O3 polymerized the network of the studied glasses. The decrease in the fraction N4 indicates this process. It was found that the γ-ray attenuation parameters [the half value layer HVL, the tenth value layer TVL, the mean free path MFP, the linear attenuation coefficient μ and the mass attenuation coefficient μm ] at the energy of 661.7 keV and the density ρ decreases with increasing the TiO2 contents on the prepared glasses. The size of the ortho -positronium hole volume ( o -Ps) (obtained from PAL) with its contents decrease with increasing the TiO2 concentration as a result of filling the hole with TiO2 . There is a fair agreement between density, relative fractional of the o -Ps open hole size and mass attenuation coefficient μm of the glass samples. The acquired results indicated a formation of non-bridging oxygens associated with the borosilicate network, which decreases its rigidity and thus, decreases its preceding physical parameters. Highlights: A creation of BO4 on the expense of BO3 and BiO3 on Na2 O-B2 O3 –PbO–SiO2 –Bi2 O3 glasses. γ-ray attenuation parameters and the density decrease with increasing TiO2 contents. The size of the o -Ps open hole decreases with increasing the TiO2 concentration. Good correlations between the relative fraction of the open hole size with ρ and μm . Important role played by the open hole size in the physical properties in glasses.